Dynamics of suspended sediment delivery to the Eastern Mediterranean continental shelf. Issue 7 (17th April 2012) - Vachtman, Dina; Sandler, Amir; Greenbaum, Noam; Herut, Barak
Abstract This study provides data on the fluvial sediment transport at the Eastern Mediterranean, an area in which the regional importance for comparative study has often been raised by investigators but the data are rather scarce. We analysed long‐ and short‐term hydrologic and sedimentological data from one of the largest coastal streams of Israel, Qishon River (1100 km2), and its estuarine environment. The results indicate that during 65 years (1944–2009), a total 140 floods have contributed to the sea an amount of approximately 2.58 × 106 tons of sediment. During this period, (i) the number of floods with a return period of more than 10 years has almost doubled during the last 30 years, and (ii) the mean annual discharge during last 10 years increased by approximately 175%. The analysis of the short (2 years) hydrological and sediment data revealed that approximately 30% of the upstream channel loads do not reach the river mouth and are deposited along the channel bed, even during major flood events. This observation was attributed largely to the facts that the lower river bed is incised below sea level, to the very low slopes and to the correspondingly low stream power and transport capacity. The results of this study highlight the effect of interchannel dynamics as well as the constraints of interaction between fluvial system and estuarine processes on sediment transport. Copyright © 2012 John Wiley & Sons, Ltd.